Hypomagnesemia - Rondón-Berríos, Helbert (2006)
Magnesium is the fourth-most abundant cation in the human body and the second-most abundant intracellular cation after potassium. Magnesium is pivotal in the transfer, storage, and utilization of energy as it regulates and catalyzes more than 300 enzyme systems. Hypomagnesemia may thus result in a variety of metabolic abnormalities and clinical consequences. Hypomagnesemia is a common electrolyte abnormality in hospitalized patients. It results from an imbalance between gastrointestinal absorption and renal excretion of magnesium. The main consequence related directly to hypomagnesemia is cardiovascular arrhythmias and if this not recognized and treated it might be fatal. When urgent correction of hypomagnesemia is required, the intravenous route should be used. Oral magnesium preparations are available for chronic use. In this article I review hypomagnesemia with emphasis on the molecular mechanisms responsible for abnormalities in magnesium homeostasis, differential diagnosis and appropriate therapy.